1979
DOI: 10.1111/j.1365-246x.1979.tb03771.x
|View full text |Cite
|
Sign up to set email alerts
|

The 1976 August 16, Mindanao, Philippine earthquake (Ms = 7.8) - evidence for a subduction zone south of Mindanao

Abstract: Summary. The Philippine earthquake of 1976 August 16, is one of the largest to have occurred world‐wide in recent years (Mw=8.8; Ms=7.8; seismic moment, Mo= 1.9 × 1028dyne‐cm). It is, however, associated not with the Philippine Trench, which is the dominant tectonic feature along the eastern Philippine Islands, but with a much less prominent trench system in the Moro Gulf, North Celebes Sea, south of Mindanao. In this area most of the seismicity is at depths greater than 500 km, associated with the westward di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 15 publications
(9 reference statements)
0
16
0
Order By: Relevance
“…Aftershocks clearly define the underthrust plane in section E of Figure 5. Stewart and Cohn [1977] suggested that the main aftershock (event 48 in Figure 6) can be interpreted as tear faulting at the northwestern end of the Cotabato Trench, although the geometry implied by this is not clear. Further south along the trench and beneath the Sangihe Ridge are two high-angle thrust faults (events 64 and 67 in Figure 6) that could be interpreted as the initiation of eastward underthrusting, but the lack of a seismic zone makes this interpretation uncertain.…”
Section: Cotabato Island Arcmentioning
confidence: 95%
See 4 more Smart Citations
“…Aftershocks clearly define the underthrust plane in section E of Figure 5. Stewart and Cohn [1977] suggested that the main aftershock (event 48 in Figure 6) can be interpreted as tear faulting at the northwestern end of the Cotabato Trench, although the geometry implied by this is not clear. Further south along the trench and beneath the Sangihe Ridge are two high-angle thrust faults (events 64 and 67 in Figure 6) that could be interpreted as the initiation of eastward underthrusting, but the lack of a seismic zone makes this interpretation uncertain.…”
Section: Cotabato Island Arcmentioning
confidence: 95%
“…The lack of an active volcanic arc, along with the short length of the inclined seismic zone, suggest that subduction began relatively recently. Stewart and Cohn [1977] and Acharya [1978] demonstrated that eastward directed underthrusting occurred in the large (M., = 7.8) earthquake of 1976 (event 58 in Figure 6 and in section E of Figure 5) . Aftershocks clearly define the underthrust plane in section E of Figure 5.…”
Section: Cotabato Island Arcmentioning
confidence: 98%
See 3 more Smart Citations